Quadrature wavelength scanning interferometry - Moschetti, Giuseppe; Forbes, Alistair; Leach, Richard K.; Jiang, Xiang; O’Connor, Daniel (Optical Society of America, 2016)
A novel method to double the measurement range of wavelength scanning interferometry (WSI) is described. In WSI the measured optical path difference (OPD) is affected by a sign ambiguity, i.e. from an interference signal it is not possible to distinguish whether the OPD is positive or negative. The sign ambiguity can be resolved by measuring an interference signal in quadrature. A method to obtain a quadrature interference signal for WSI is described and a theoretical analysis of the advantages is reported. Simulations of the advantages of the technique and of signal errors due to non-ideal quadrature are discussed. The analysis and simulation are supported by experimental measurements to show the improved performances.